Kinetic separation of landfill gas by a two-bed pressure swing adsorption process packed with carbon molecular sieve: Nonisothermal operation - Kim, Min-Bae; Bae, Youn-Sang; Choi, Dae-Ki; Lee, Chang-Ha (AMER CHEMICAL SOC, 2006)
To produce pipeline-quality methane with a high level of adsorbent productivity from landfill gas, the pressure swing adsorption (PSA) process with carbon molecular sieve (CMS) was investigated experimentally and theoretically by using CO2/CH4 feed (50/50 vol%). Due to the high throughput as well as the high heat of adsorption of the faster diffusing component (CO2), the isothermal assumption was no longer valid and energy balance equations were inevitable for accurate prediction. Owing to the strong concentration dependency of sorption rate, the adsorption dynamics of the CMS bed in the PSA process were predicted by using a modified LDF model with concentration-dependent diffusivity. The nonisothermal and nonadiabatic model successfully predicted the performance of the CMS PSA process, which was operated by the Skarstrom cycle with cocurrent equalization. The purity was significantly affected by the changes in the adsorption pressure and adsorption step time, while the change in the recovery due to these operating variables was relatively small. The purge-to-feed ratio played a key role in improving the productivity based on the production of 90+% CH4 from the CH4/CO2 mixture.
Keywords: NUMERICAL-SIMULATION; OXYGEN; DIFFUSION; SORPTION; DIOXIDE; DYNAMICS; AIR; PSA